Analysis of Process Performance Indicators - An Applied Study at Al-Furat General Company for Chemical Industries - Ghassan Qassem Daoud Al-Lami,; Mahmod Fahad Abd Ali, (Iraqi Journal for Administrative Sciences, 2025)
Focus on production operation is regarded a decision factor to achieve continual competitive advantage which leads to the fulfillment of consumer satisfaction which in turn , leads to the success of the organization , industrial companies contain many variables basic operations and sub-orations . the company focuses on the goal of consumer satisfaction through satisfying the requirements that the consumer wishes to get of the product in a way that increases the company's returns . The hypothesis of the study is that there significant difference among the factories , which are the study sample , in the indices of process performance , represented by the indexes of cycle time , production rate , cushion , production , efficiency , utilization rate. The statistical results for the data presented a significant supply for the study hypothesis . The study reached at many conclusions , the most important of which is that there are significant differences among the factories of the company toward the indexes of process performance , which has been asserted by the results of the analysis of these indexes by virtue of real data fixed in the companies records . The study recommends that is necessary to review the technological paths for all products , beginning with design and ending with the activities of manufacturing and storing for the purpose of alimenting and canceling surplus activities or the low add-value , which would have positive reflections on the reduction of production cycle time and the increase of the whole time for the product.